2020
DOI: 10.1111/twec.12910
|View full text |Cite
|
Sign up to set email alerts
|

Reassessing the foreign ownership wage premium in Germany

Abstract: This paper evaluates the effect of foreign takeover on wages of workers in German establishments, using rich linked employer–employee data from 2003 to 2014. To identify a causal effect of foreign takeover, we combine propensity‐score matching with a difference‐in‐difference estimator. We find that a takeover by a foreign investor leads to a wage premium of 4.0 log points in the year after ownership change, which further increases to 6.3 log points 3 years after acquisition. The wage premium is largest for hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…Girma and Görg (2007), studying the United Kingdom, find that foreign-owned firms pay higher wages than comparable domestic firms, and the magnitude of these wage premia differs for skilled and unskilled workers. Egger et al (2020) provide evidence for a foreign ownership wage premium in Germany. They also show that this wage premium differs by skill group.…”
Section: Literature Reviewmentioning
confidence: 93%
“…Girma and Görg (2007), studying the United Kingdom, find that foreign-owned firms pay higher wages than comparable domestic firms, and the magnitude of these wage premia differs for skilled and unskilled workers. Egger et al (2020) provide evidence for a foreign ownership wage premium in Germany. They also show that this wage premium differs by skill group.…”
Section: Literature Reviewmentioning
confidence: 93%
“…Although rising productivity is likely to result in higher wages, many studies have suggested disparities in the impact on wages (Hijzen et al, 2013;Setzler and Tintelnot, 2021). Using German data, Egger et al (2020) revealed that the wage premiums of foreign affiliates are concentrated in high-skilled workers, suggesting that the wage gap between high-and low-skilled workers will widen. Considering the possibility of such disparities, the impact of inward FDI on wages and employment would vary depending on the individual's skills, and as a result, individuals' preferences for inward FDI may differ.…”
Section: Economic Attributesmentioning
confidence: 99%
“…They employ a DID method implemented in a regression framework (Conyon et al, 2002, p. 7). Elsewhere, Egger et al (2020) estimate the foreignownership wage premium in Germany, using a longitudinal linked employer-employee data. Their study findings indicate positive effects of foreign acquisition on wages.…”
Section: Empirical Literaturementioning
confidence: 99%